دراسة تحليلية لبعض شروط ومعايير نجاح تكوين لاعبي كرة القدم في المستوى العالي - دحامنية نور الإسلام (My University, 2025)
Abstract: The study is entitled "An Analytical Study of Some Conditions and Criteria for the Success of Training Football Players at the High Level", and through a field study conducted at the level of the clubs of the Algerian Professional Football League One and Two, the study aims to know whether some criteria and conditions contribute to the success of training football players at the high level?, by studying the role played by effective planning, psychological preparation, analysis of sports performance, and the role played by sports medicine in the success of the training process, where the researchers applied the descriptive survey method due to its suitability to the subject of the study, on a community represented by coaches and players of Algerian professional clubs for different categories and age groups (schools/buds/juniors/cubs/seniors), and it was applied to a sample selected randomly that included by 150 coaches for different categories and age groups and 1500 players from the various previous age groups, where the questionnaire was used in the study as a research tool (a questionnaire directed to coaches and another directed to players), where the statistical methods used in The tool analysis includes Cronbach's alpha method, split-half method, frequencies, percentage, and Chi-Square Goodness of Fit Test, to reach the researchers in the end the fact that effective sports planning plays a crucial role in the success of the formation of football players, as it contributes to improving performance, developing skills, and achieving sports goals, and psychological preparation is necessary to enhance self-confidence and deal with pressure. In addition, performance analysis helps in identifying strengths and weaknesses and designing customized training programs, and sports medicine ensures the safety of players and contributes to preventing injuries and accelerating the rehabilitation process, to finally reach the development of individual and group training plans based on specific goals, providing training programs to enhance self-confidence and focus. Using modern performance analysis techniques to identify strengths and weaknesses, and providing periodic medical examinations for players. الملخص : الدراسة تحت عنوان "دراسة تحليلية لبعض شروط ومعايير نجاح تكوين لاعبي كرة القدم في المستوى العالي"، وبدراسة ميدانية تمت على مستوى أندية الرابطة المحترفة الأولى والثانية الجزائرية لكرة القدم، تهدف الدراسة الى معرفة ما هل تساهم بعض المعايير والشروط في نجاح تكوين لاعبي كرة القدم في المستوى العالي؟، من خلال دراسة الدور الذي يلعبه التخطيط الفعال، التحضير النفسي، تحليل الأداء الرياضي، والدور الذي يلعبه الطب الرياضي في نجاح العملية التكوينية، حيث طبق الباحثين المنهج الوصفي المسحي نظرا لملاءمته موضوع الدراسة، على مجتمع تمثل في المدربين ولاعبي الأندية المحترفة الجزائرية لمختلف الأصناف والفئات السنية(مدارس/براعم/أصاغر/أشبال/أكابر) ، وطبقت على عينة اختيرت بشكل عشوائي شملت 150 مدربا لمختلف الأصناف والفئات السنية و 1500 لاعبامن مختلف الفئات السنية السابقة، حيث استخدم في الدراسة الاستبيان كأداة بحث (استبيان موجه للمدربين وآخر موجه للاعبين)، حيث كانت الوسائل الإحصائية المتبعة في تحليل الأداة تشمل كل من طريقة ألفا كرونباخ، وطريقة التجزئة النصفية، التكرارات، النسبة المئوية، واختبار جودة المطابقة Chi-Square Goodness of Fit Test، ليتوصل الباحثين في الأخير الى حقيقة أن التخطيط الرياضي الفعال يلعب دورا حاسما في نجاح تكوين لاعبي كرة القدم، حيث يساهم في تحسين الأداء وتطوير المهارات وتحقيق الأهداف الرياضية، كما أن التحضير النفسي ضروري لتعزيز الثقة بالنفس والتعامل مع الضغوط. بالإضافة إلى ذلك، يساعد تحليل الأداء في تحديد نقاط القوة والضعف وتصميم برامج تدريبية مخصصة ، ويضمن الطب الرياضي سلامة اللاعبين ويساهم في الوقاية من الإصابات وتسريع عملية التأهيل، ليتصلوا في الأخير الى وضع خطط تدريبية فردية وجماعية مبنية على أهداف محددة، توفير برامج تدريبية لتعزيز الثقة بالنفس والتركيز، استخدام تقنيات تحليل الأداء الحديثة لتحديد نقاط القوة والضعف، وتوفير فحوصات طبية دورية للاعبين. Résumé : L'étude, intitulée « Analyse des conditions et critères de réussite de la formation de footballeurs de haut niveau », a été menée auprès des clubs des ligues professionnelles algériennes de première et deuxième division. Elle vise à déterminer si certains critères et conditions contribuent à la réussite de la formation de footballeurs de haut niveau, en étudiant le rôle d'une planification efficace, d'une préparation psychologique adéquate, de l'analyse de la performance sportive et du rôle de la médecine du sport dans le processus d'entraînement. Les chercheurs ont appliqué la méthode d'enquête descriptive, adaptée au sujet de l'étude, auprès d'une communauté composée d'entraîneurs et de joueurs de clubs professionnels algériens de différentes catégories et tranches d'âge (écoles, jeunes, juniors, cadets, seniors). L'échantillon, sélectionné aléatoirement, comprenait 150 entraîneurs et 1 500 joueurs. Un questionnaire (un pour les entraîneurs et un autre pour les joueurs) a servi d'outil de recherche. L'analyse statistique a été réalisée à l'aide du coefficient alpha de Cronbach. L'utilisation de méthodes telles que la méthode de la moitié-moitié, les fréquences, les pourcentages et le test d'adéquation du Chi-deux a permis aux chercheurs de conclure qu'une planification sportive efficace joue un rôle crucial dans la réussite de la formation des joueurs de football. Elle contribue en effet à améliorer les performances, à développer les compétences et à atteindre les objectifs sportifs. La préparation psychologique est également essentielle pour renforcer la confiance en soi et gérer la pression. De plus, l'analyse des performances aide à identifier les forces et les faiblesses et à concevoir des programmes d'entraînement personnalisés. La médecine du sport garantit la sécurité des joueurs, contribue à prévenir les blessures et accélère le processus de rééducation. L'objectif final est d'élaborer des plans d'entraînement individuels et collectifs basés sur des objectifs spécifiques, proposant des programmes visant à renforcer la confiance en soi et la concentration. Enfin, des techniques modernes d'analyse des performances sont utilisées pour identifier les forces et les faiblesses, et des examens médicaux périodiques sont proposés aux joueurs.
Keywords: Success criteria and conditions; Player; Formation; Footbal; High level; معايير وشروط النجاح; التكوين; اللاعب; كرة القدم; المستوى العالي; Critères et conditions de réussite; Joueur de football de haut niveau.; formation